Hepatic Hippo signaling inhibits protumoural microenvironment to suppress hepatocellular carcinoma. Issue 9 (2nd September 2017) - Kim, Wantae; Khan, Sanjoy Kumar; Liu, Yuchen; Xu, Ruoshi; Park, Ogyi; He, Yong; Cha, Boksik; Gao, Bin; Yang, Yingzi
Abstract : Objective: Hippo signalling is a recently identified major oncosuppressive pathway that plays critical roles in inhibiting hepatocyte proliferation, survival and hepatocellular carcinoma (HCC) formation. Hippo kinase (Mst1 and Mst2) inhibits HCC proliferation by suppressing Yap/Taz transcription activities. As human HCC is mainly driven by chronic liver inflammation, it is not clear whether Hippo signalling inhibits HCC by shaping its inflammatory microenvironment. Design: We have established a genetic HCC model by deleting Mst1 and Mst2 in hepatocytes. Functions of inflammatory responses in this model were characterised by molecular, cellular and FACS analysis, immunohistochemistry and genetic deletion of monocyte chemoattractant protein-1 ( Mcp1 ) or Yap . Human HCC databases and human HCC samples were analysed by immunohistochemistry. Results: Genetic deletion of Mst1 and Mst2 in hepatocytes (DKO) led to HCC development, highly upregulated Mcp1 expression and massive infiltration of macrophages with mixed M1 and M2 phenotypes. Macrophage ablation or deletion of Mcp1 in DKO mice markedly reduced hepatic inflammation and HCC development. Moreover, Yap removal abolished induction of Mcp1 expression and restored normal liver growth in the Mst1/Mst2 DKO mice. Finally, we showed that MCP1 is a direct transcription target of YAP in hepatocytes and identified a strong gene expression correlation between YAP targets and MCP-1 in human HCCs. Conclusions: Hippo signalling in hepatocytes maintains normal liver growth by suppressing macrophage infiltration during protumoural microenvironment formation through the inhibition of Yap-dependent Mcp1 expression, providing new targets and strategies to treat HCCs.